Homestay enterprises as vehicles for women’s economic empowerment: Intent, challenges, and opportunities in remote Cagayan Valley - Joan Minia Nebrida (Journal of Rural Tourism, 2025)
Purpose -  This study aims to examine the lived experiences of women-led homestay operators in the Cagayan Valley, Philippines, by exploring their motivations, challenges, and the opportunities emerging from their participation in homestay enterprises. Method - A qualitative research design was employed, using semi-structured interviews with 12 women actively managing homestays. Thematic analysis was conducted to identify core patterns related to motivation, operational constraints, skill development, and socio-cultural dynamics. Findings - The analysis reveals that economic empowerment, personal growth, skill development, and social recognition are the key motivations driving women’s engagement in homestay operations. Participants reported increased income, enhanced confidence, and improved competencies in hospitality management, marketing, and interpersonal communication. However, they also faced structural and socio-cultural barriers, including inadequate infrastructure, financial limitations, skill gaps, and heavy household responsibilities. Despite these constraints, women-led homestays generated positive community outcomes such as cultural promotion through collaborations with artisans and farmers, strengthened social visibility, and expanded livelihood opportunities. Originality/Value - This study provides nuanced insights into the transformative potential of women-led homestays as vehicles for inclusive rural development. By illuminating both empowerment pathways and persistent gendered challenges, it contributes valuable evidence for policymakers and development practitioners seeking to design targeted interventions—such as training programs, financial support mechanisms, and infrastructure improvements to enhance the sustainability and impact of women-driven tourism enterprises.